2019
DOI: 10.1007/s10853-019-04116-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the oxidizing agent in the synthesis of graphite oxide

Abstract: The oxidation capacity of several procedures described in the literature which use different oxidizing agents has been exhaustively studied in order to describe the best route for oxidation of this material. The oxidation capacities of different types of materials were evaluated in the synthesis of graphite oxide in an effort to obtain a product with similar characteristics to those provided by commonly employed methods. The results obtained show that graphite oxide structures are greatly influenced by the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Figure presents together the transmittance FT-IR spectra of bare and encapsulated K 2 FeO 4 . In the case of the former (Figure a), a primary peak appeared at 808 cm –1 along with a shoulder peak at 780 cm –1 , which was the characteristic peak of FeO 4 . In the case of the latter (Figure b), the spectrum showed the characteristics peaks of the shell materials. The characteristic peak at 1100 cm –1 arose from ethyl cellulose, and those centered around 2916, 1471, and 720 cm –1 belong to the stretching and bending vibrations of paraffin wax .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure presents together the transmittance FT-IR spectra of bare and encapsulated K 2 FeO 4 . In the case of the former (Figure a), a primary peak appeared at 808 cm –1 along with a shoulder peak at 780 cm –1 , which was the characteristic peak of FeO 4 . In the case of the latter (Figure b), the spectrum showed the characteristics peaks of the shell materials. The characteristic peak at 1100 cm –1 arose from ethyl cellulose, and those centered around 2916, 1471, and 720 cm –1 belong to the stretching and bending vibrations of paraffin wax .…”
Section: Resultsmentioning
confidence: 95%
“…Sofer et al 19 claimed that K 2 FeO 4 was unable to oxidize graphite and attributed the little oxidation (∼1.9% oxygen detected by XPS) of the graphite surface to some impurities such as KNO 3 and KClO 3 present in the original commercial K 2 FeO 4 . In another comparative study on the effects of different oxidizing agents, 20 ferrate was found to be only capable of oxidizing graphite to low extents (10−15%).…”
Section: T H Imentioning
confidence: 98%
“…However, after oxidation and subsequent mechanical exfoliation, several oxygenated groups can be observed, which are the same in both oxides. The first observable peak between 3600 and 3000 cm − 1 , was attributed to the O-H stretching vibrations of the hydroxyl groups [40]. Another related peak for the hydroxyl groups was located at 1450 cm − 1 and in this case, it was related to the bending vibration of carboxylic acid groups attached to the edge of the structure.…”
Section: Adsorbent Characterizationmentioning
confidence: 88%
“…The disappearance of some minor peaks on petcoke after acid treatment demonstrates the removal of the mineral impurities, whereas the broadening of the peak associated with graphite (002) suggests destruction of the structure through oxidation by the acids and increased disorder of the stacking of graphene [43,44]. The shift in the graphite peak (002) in the patterns of samples P-N-24 and P-N/S-24 to lower 2θ values is consistent with increased distance between the layers as a result of the formation of oxygen-containing groups [44,45]. Similarly, a peak at ~10° 2θ on P-N-24 is assigned to the graphene oxide structure (001) [43,45], which infers a larger interlayer spacing and greater oxidation consistent with this sample having the highest oxygen content (Table 1).…”
Section: Physical Properties Of Petcoke Treated With Various Acidsmentioning
confidence: 99%
“…The weak and broad peak at 20-30 • 2θ indicates that petcoke contains a combination of amorphous and graphitic (002) structures. The disappearance of some minor peaks on petcoke after acid treatment demonstrates the removal of the mineral impurities, whereas the broadening of the peak associated with graphite (002) suggests destruction of the structure through oxidation by the acids and increased disorder of the stacking of graphene [43,44]. The shift in the graphite peak (002) in the patterns of samples P-N-24 and P-N/S-24 to lower 2θ values is consistent with increased distance between the layers as a result of the formation of oxygen-containing groups [44,45].…”
Section: Physical Properties Of Petcoke Treated With Various Acidsmentioning
confidence: 99%